Transformasi Limbah Tulang Ikan Cucut Menjadi Penyedap Rasa Ikan (PERAKAN) Bernilai Ekonomi di Pulau Buluh: Analisis Harga Jual, HPP, dan BEP - Aprilia, Andi Naswa; Chusnul Khotimah; Sheftia Endrika; Riri Zelmiyanti (CV. Ulil Albab Corp, 2025)
`The PERAKAN (Fish Flavoring) program aims to educate the Buluh Island community in utilizing spiny fish bone waste into economically valuable fish flavoring products. The program is conducted through a series of structured activities, starting from boiling, drying, mashing, to packaging the final product. This integrated approach successfully improved the community's knowledge and skills, and positively impacted their welfare by creating new opportunities, reducing waste, and increasing income. The evaluation showed that 100% of participants understood the entire process of processing spiny fish bones into saleable products. This success opens up opportunities for the development of the PERAKAN program in other areas of Indonesia. Support from the government, non-governmental organizations, and the fisheries sector is essential to ensure the sustainability of this program. Thus, PERAKAN has the potential to expand its impact, utilizing natural resources sustainably throughout Indonesia.